Comparison of double (360 mg) ticagrelor loading dose with standard (60 mg) prasugrel loading dose in ST-elevation myocardial infarction patients: The Rapid Activity of Platelet Inhibitor Drugs (RAPID) primary PCI 2 study - Parodi, Guido; Bellandi, Benedetta; Valenti, Renato; Migliorini, Angela; Marcucci, Rossella; Carrabba, Nazario; Giurlani, Letizia; Gensini, Gian Franco; Abbate, Rosanna; Antoniucci, David (The American heart journal, 2014)
In ST-elevation myocardial infarction (STEMI) patients, residual platelet reactivity soon after a loading dose (LD) of prasugrel or ticagrelor is higher than that reported for healthy volunteers or subjects with stable coronary artery disease; and the majority of primary percutaneous coronary intervention (PPCI) procedures with bivalirudin monotherapy are performed without proper platelet inhibition. However, ticagrelor LD is just the daily dose, whereas prasugrel LD is 6-fold the long-term daily dose. We hypothesized that an increased ticagrelor LD may result in a faster and more effective platelet inhibition as compared with the standard prasugrel LD. Fifty patients with STEMI, pretreated with intravenous aspirin, undergoing PPCI were randomized to receive prasugrel 60-mg LD (n = 25) or ticagrelor 360-mg LD (n = 25). Residual platelet reactivity was assessed by VerifyNow at baseline and 1, 2, 4, and 12 hours after drug LD. At the time of LD, 90% of enrolled patients had an aspirin reactivity unit value <550. P2Y12 reaction units 1 hour after the LD (study primary end point) were 236 (129-289) and 248 (115-304) in the prasugrel and ticagrelor group, respectively (P = .899). High residual platelet reactivity (P2Y12 reaction units ≥240) was found in 43% and 56% of patients (P = .386) at 1 hour and in 30% and 32% of patients (P = .907) at 2 hours, respectively. There was no significant difference in bleeding, arrhythmias, or dyspnea episodes in the 2 groups. In patients with STEMI undergoing PPCI, double (360 mg) ticagrelor LD failed to achieve a faster and more intense platelet inhibition as compared with the standard prasugrel LD. Intravenously administered aspirin allowed to achieve a very early inhibition of acid arachidonic pathway.